A reavaliação da doutrina das unidades no Preface to Shakespeare (1765) : o prenúncio da ruptura com o Ancien Régime - Castro, Diego de (2016)
The objective of this dissertation is demonstrate by means of a dialectical reading of Preface to Shakespeare (1765) by Samuel Johnson (1709-1784), that the reassessment of the doctrine of the units (action, time and place) no solely unveil the breaking of the English literary criticism with the classical aesthetic but the sign of a deep breaking of the English capitalist society from the eighteenth century with Ancien Régime. The issue (the reassessment of the doctrine of the units) consists in the defense that Johnson does in favor of Shakespeare's plays against the censures of other neoclassical critics, these influenced by French classicism. The defense that English critic undertook in favor of the English poet‘s dramas against the reproaches of neoclassical critics anticipated the rupture of the English criticism with the classical aesthetic. The proposal is treating of the literary and philosophical aspects involved in the chief theme, at last to amplify the horizon of reading through of the notions of structure of feeling by Raymond Williams (1977) and political unconscious by Jameson (1992).